Thermomechanical–microstructural modelling of nodular cast iron solidification - Celentano, Diego Javier (2013)
This paper presents a thermomechanical–microstructural formulation for the analysis of the solidification process of nodular cast irons of eutectic composition. This formulation is defined in a finite strain thermoplasticity framework considering multinodular microstructure based liquid– solid phase change effects. The performance of this model is evaluated in the analysis of a solidification test for which some laboratory measurements are available. Computed temperature and displacement evolutions together with final values of austenite and graphite volumetric fractions and density of graphite nodules are all found to reasonably agree with the corresponding experimental measurements. This analysis illustrates the possibility of tackling different coupled and complex phenomena occurring in casting problems.